2022
DOI: 10.1038/s41467-022-30314-7
|View full text |Cite
|
Sign up to set email alerts
|

POWR1 is a domestication gene pleiotropically regulating seed quality and yield in soybean

Abstract: Seed protein, oil content and yield are highly correlated agronomically important traits that essentially account for the economic value of soybean. The underlying molecular mechanisms and selection of these correlated seed traits during soybean domestication are, however, less known. Here, we demonstrate that a CCT gene, POWR1, underlies a large-effect protein/oil QTL. A causative TE insertion truncates its CCT domain and substantially increases seed oil content, weight, and yield while decreasing protein con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 67 publications
0
72
1
Order By: Relevance
“…Furthermore, some soybean sugar transporters such as GmSWEET10a, GmSWEET10b and GmSWEET39 had pleiotropic effect on seed protein and oil content (Miao et al2020;Wang et al 2020b;Zhang et al 2020). POWR1 (Protein, Oil, Weight, Regulator 1) gene plays a critical role in controlling the seed quality and yield traits by regulating likely nutrient transport and lipid metabolism, and transgenic study demonstrated that the high-protein POWR1 allele may be employed to meet the worldwide requirement for high-protein soybean in the breeding process (Goettel et al 2022).…”
Section: Soybean Protein Content-related Genesmentioning
confidence: 99%
“…Furthermore, some soybean sugar transporters such as GmSWEET10a, GmSWEET10b and GmSWEET39 had pleiotropic effect on seed protein and oil content (Miao et al2020;Wang et al 2020b;Zhang et al 2020). POWR1 (Protein, Oil, Weight, Regulator 1) gene plays a critical role in controlling the seed quality and yield traits by regulating likely nutrient transport and lipid metabolism, and transgenic study demonstrated that the high-protein POWR1 allele may be employed to meet the worldwide requirement for high-protein soybean in the breeding process (Goettel et al 2022).…”
Section: Soybean Protein Content-related Genesmentioning
confidence: 99%
“…20 (Diers et al, 1992;Hwang et al, 2014;Warrington et al, 2015), and it has received extensive attention because of its high additive effects and stability (Diers et al, 1992;Wang et al, 2015;Li et al, 2019;Samanfar et al, 2019;Zhang W et al, 2019;Li et al, 2021;Goettel et al, 2022). Glyma.20G085100 (POWR1) was recently reported as a causative gene of chr20 QTL; a transposable element insertion in its conserved CCT domain produced seeds with increased oil content and weight and decreased PC (Goettel et al, 2022). However, few QTL or genes related to PC have been applied in breeding due to…”
Section: Discussionmentioning
confidence: 99%
“…The 100-seed weight is an important yield-related trait, and also one of the targets under selection during soybean domestication (Duan et al 2022;Goettel et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the natural variations of three genes were found associated with soybean seed size/weight, including GmST1, GmST5, and POWR1 (Duan et al 2022;Goettel et al 2022;Li et al 2022). Both GmST1 (Glyma.08g109100, encoding a UDP-D-glucuronate 4-epimerase) and GmST05 (Glyma.05G244100, encoding a member of the FT and TFL1 family of phosphatidylethanolamine-binding protein) function as positive regulators of seed thickness, seed length, seed width, and 100-seed weight in soybean (Duan et al 2022;Li et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation